Psychiatric morbidity among patients in cardiac outpatient department (Bangladesh Journal of Psychiatry, 2017)
Psychiatric morbidity among patients attending cardiac outpatient department has been revealed as a significant problem in many studies. The objective of this study was to determine the proportion of psychiatric morbidity among cardiac outdoor patients in National Institute of Cardio-Vascular Diseases (NICVD), Dhaka. It was a cross-sectional study conducted from September 2015 to February 2016 among the purposively selected patients of NICVD outdoor. Convenient sampling technique was used to select 151 patients aged 18 to 65 years who were attending the cardiac outpatient department in NICVD, Dhaka. A semi-structured questionnaire including Self-Reporting Questionnaire (SRQ) was used to screen psychiatric symptoms. Results showed that the mean (+SD) age of the patients was 46.09 (+11.17) years and majority of the respondents (60.9%) were male. The most common cardiac morbidity was ischemic heart disease (29.8%). Among all the respondents, 21.9% were suffering from psychiatric disorders. Maximum of the cases were diagnosed with major depressive disorder (11.3%). Thus, it was apparent that psychiatric morbidity was commonly present in patients who attended cardiac outpatient departments.Bang J Psychiatry June 2015; 29(1): 1-4